A compact inchworm piezoelectric actuator with high speed: Design, modeling, and experimental evaluation. (1st February 2023) - Ma, Xuefeng; Liu, Yingxiang; Deng, Jie; Gao, Xiang; Cheng, Jianfei
Highlights: Only two PSAs are used to realize the step-by-step motion of an inchworm PA. A new working principle is proposed to realize four steps in one cycle. The inchworm PA achieves high output speed of millimeter per second. Step with no backward motion is achieved even under a large carrying load. Abstract: Inchworm piezoelectric actuators are usually composed of three or more piezoelectric stacks, which makes their structures and circuits sophisticated. Although a variety of inchworm piezoelectric actuators driven by fewer piezoelectric stacks have been proposed to realize the simplification of the traditional structures. It is still difficult to inherit the advantage of large output force and achieve high output speed without backward motion for a simplified inchworm actuator. Here, we present a compact inchworm piezoelectric actuator with two multi-function driving feet, in which only two piezoelectric stacks are utilized. The deformations of the driving feet are utilized efficiently by the proposed working principle, and four steps in each cycle are realized, which improve the output speed of the proposed actuator. The stiffness optimization is carried out to obtain a stable step characteristic and a high output force. Under a voltage of 150 V and a frequency of 50 Hz, the actuator achieved a maximum speed of 2081.16 μm/s, a carrying load larger than 6.442 kg and an output force of 14 N. Furthermore, this actuator also achieved a stable step process without backward motion under a carrying load of 6.442 kg.